2023
DOI: 10.52380/mojet.2023.11.2.466
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effect of Increased Screen Usage Time on Preschoolers' Cognitive Process Skills During Covid 19 Period

Abstract: Today, due to various factors such as facilitation of access to digital technologies, widespread internet use, rapidly increasing urbanization, and digitization of education, children meet the screen at a much earlier age and screen usage times increase rapidly. Due to the COVID-19 pandemic affecting the whole world, the introduction of distance education has been another important factor that increases screen usage time. According to the results of the research, long-term screen use can cause eye health probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The impact of heightened screen exposure on cognitive processing skills in preschoolers during the COVID-19 period was investigated by Sapsa glam and Birak [21]. Their findings indicated that excessive screen time can hinder children's concentration on educational activities, leading to shorter attention spans and reduced engagement.…”
Section: Children's Internet Use Post-pandemicmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of heightened screen exposure on cognitive processing skills in preschoolers during the COVID-19 period was investigated by Sapsa glam and Birak [21]. Their findings indicated that excessive screen time can hinder children's concentration on educational activities, leading to shorter attention spans and reduced engagement.…”
Section: Children's Internet Use Post-pandemicmentioning
confidence: 99%
“…Most recent studies were based on the perceptions of teachers and parents, which means that students are heard less frequently. Furthermore, it was noted, above all, that the pandemic period has changed the form and purpose of Internet use by children and has increased and diversified the ways of learning [26,27], but it has also contributed to an increased time of exposure to screens [21] and, consequently, the risks of this use when unsupervised [23].…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation